Brilliant bees - Glaser, Linda; Holland, Gay W. (Brookfield, Conn. : Millbrook Press, 2003)
Simple text and illustrations describe the physical characteristics, habits, and life cycle of the honey bee.
Wilson's Children.
School Library Journal.
Booklist.
3.6
K-3
Keywords: Honeybee -- Juvenile literature; Honeybee; Bees; Honeybees; Bees; Honeybee; Bees